COMPARATIVE STUDY OF ANTI-CANCER ACTIVITY OF APREMILAST AND IMATINIB – IN VITRO STUDY OF COLON CANCER - PARVATHAREDDY SOWMYA; BALAJI C; PAREPALLI SURESH; KAVITHA RAMASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Among oral phosphodiesterase (PDE) inhibitors, PDE-4 inhibitors such as apremilast display anti-inflammatory effects in numerous in vitro and in vivo studies. Apremilast suppresses the release of various cytokines, interleukins, and other inflammatory mediators, while also reducing the formation of reactive oxygen species. Moreover, it may act as a pro-apoptotic agent in colon and pancreatic cancer cells. Meanwhile, imatinib, a tyrosine kinase inhibitor used to treat gastrointestinal stromal tumors, chronic myeloid leukemia, and other cancers, also shows anti-cancer activity. This study evaluates the effects of both PDE-4 inhibitors and imatinib on HT-29 colon cancer cells using the MTT (methylthiazolyldiphenyl-tetrazolium bromide) assay. Methods: HT-29 cell lines are incubated at 37°C for 24 h, and drug samples are added at various concentrations. An ultraviolet spectrophotometer was used to add 1 mL of dimethyl sulfoxide. 50% inhibition concentration was measured graphically. Results: The maximum half of the cell inhibitory 56.09% is at a 31.2 μg/mL concentration of apremilast, and the maximum half of the cell inhibitory 49.17% is at a 62.5 μg/mL concentration of imatinib. Conclusion: Hence, this study concludes that the percentage of cell inhibition for apremilast is equally potent as imatinib, but at higher concentrations, the percentage of cell viability is less for imatinib than apremilast in colon cancer cell lines. Further studies might be required on humans to prove the effect of the drug on cancer patients.